MAKNA AL-SULBI DAN AL-TARA'IB (Q.S AL-TARIQ AYAT 7) DALAM TINJAUAN TAFSIR MAUDU'I DAN SEMANTIK - Miatul Qudsia dan Muhammad Faishal Haq (Program Studi Ilmu Al-Qur'an dan Tafsir, Institut Agama Islam Negeri (IAIN) Palu, 2021)
This study aims to analyze more comprehensively the meaning of the words al-sulbi and al-tara'ib. In its interpretation, the seventh verse of the letter al-Tariq is always associated with the study of the kauniyah verses, and the majority relates it to the process of human creation. In fact, if we refer to the basic meaning of both, al-s ulbi means hard or strong, and al-tara'ib means dirt or dust, it is very far from being connected to the process of human creation. To solve this problem, the writer uses the method of interpretation of maud u'i surah with the semantic approach of the Qur'an. From this analysis, the conclusion is that by using the method of interpretation of maud u'i surah and considering the munasah in the letter al-Ta>riq, then it could mean that the meaning is hard rocks (al-sulbi) and soft soil (al-tara'ib) on the crust of the earth, and is related to the discharge of water from the ground. This shows that it has nothing to do with the process of human creation. However, by using the semnatic approach of the Koran, it is found that the lafaz al-s ulbi refers to the back and al-tara>'ib leads to the ribs of women. Thus, the explanation strongly supports the results of the interpretation in general, namely the process of human creation. Thus, it can be taken into account that in general verse 7 of the letter al-Ta>riq describes the process of human creation. And on the other hand, simultaneously there are systemic similarities with the process of releasing groundwater from the aquifer.",